2020
DOI: 10.1080/14756366.2020.1713114
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins fromMagydaris pastinaceaas inhibitors of the tumour-associated carbonic anhydrases IX and XII: isolation, biological studies and in silico evaluation

Abstract: In an in vitro screening for human carbonic anhydrase (hCA) inhibiting agents from higher plants, the petroleum ether and ethyl acetate extracts of Magydaris pastinacea seeds selectively inhibited hCA IX and hCA XII isoforms. The phytochemical investigation of the extracts led to the isolation of ten linear furocoumarins (1-10), four simple coumarins (12-15) and a new angular dihydrofurocoumarin (11). The structures of the isolated compounds were elucidated based on 1 D and 2 D NMR, MS, and ECD data analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 54 publications
3
18
0
Order By: Relevance
“…Interestingly, the two studied coumarin 10 and 17 oriented the lactone moiety towards the Zn 2þ ion, creating a favourable condition for the hydrolysis. Keeping in mind these hypothetical binding modes, we can speculate that these selective inhibitors might be not capable of accessing at the active site of hCA II, that is characterised by the presence of Phe131 residue as the gatekeeper of enzymatic cleft; in the case of hCA IX or hCA XII isoforms, the residues Val131 or Ala131 replace the bulkier Phe131, respectively, thus explaining the hCA IX/hCA XII selectivity of tested coumarins 7-11, 15-16 over hCA II as found for other coumarin derivatives reported in the literature 30,45 . This issue could justify the advantageous selectivity profile showed by this class of coumarins that are lacking affinity against off-target isoforms hCA II (K i values> 10,000 nM).…”
Section: Docking Studiesmentioning
confidence: 85%
“…Interestingly, the two studied coumarin 10 and 17 oriented the lactone moiety towards the Zn 2þ ion, creating a favourable condition for the hydrolysis. Keeping in mind these hypothetical binding modes, we can speculate that these selective inhibitors might be not capable of accessing at the active site of hCA II, that is characterised by the presence of Phe131 residue as the gatekeeper of enzymatic cleft; in the case of hCA IX or hCA XII isoforms, the residues Val131 or Ala131 replace the bulkier Phe131, respectively, thus explaining the hCA IX/hCA XII selectivity of tested coumarins 7-11, 15-16 over hCA II as found for other coumarin derivatives reported in the literature 30,45 . This issue could justify the advantageous selectivity profile showed by this class of coumarins that are lacking affinity against off-target isoforms hCA II (K i values> 10,000 nM).…”
Section: Docking Studiesmentioning
confidence: 85%
“…As for all other coumarins investigated to date 6,10 , nature and position (number) of substituents on the coumarin ring were the most important factors influencing the enzyme inhibitory properties of these compounds 9 . Another, more recent study, by Fois et al 65 reported coumarins from the Sardinian plant Magydaris pastinacea ( Figure 5) acting as efficient inhibitors of the tumour-associated isoforms hCA IX and XII whereas their activity for the cytosolic isoforms hCA I and II was found to be very weak ( Table 2).…”
Section: Natural Product Coumarins Investigated As Caismentioning
confidence: 94%
“…Some of these compounds (36)(37)(38)(39)(40)(41)(42)(43)(44)(45) are in fact variously substituted furo-coumarins (psoralens), with a tricyclic ring system incorporating the furan heterocycle, and this class of NPs is well known in nature, being present in many other plants 65 . The remaining derivatives incorporate isoprenyl-, hydrated isoprenyl-or polyprenylated moieties, also typical for many NPs 65 . It is interesting to note that all coumarins/furocoumarins 36-45 were ineffective as hCA I and II inhibitors, whereas they showed a rather good, high nanomolar inhibitory action against the tumour-associated isoforms hCA IX and XII (Table 2) 65 .…”
Section: Natural Product Coumarins Investigated As Caismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, no direct interaction with the metal ion or with the zinc coordinated water was observed, as the inhibitor was located far away from the bottom of the active site, occluding its entrance. This binding mode and inhibition mechanisms are rather extravagant per se, considering just the structural features mentioned above, but it was thereafter observed that they lead to a highly desired inhibition profile for this type of compounds: the possibility to design highly isoform-selective inhibitors for the different human isoforms [1,[6][7][8][63][64][65][66][67][68][69][70][71]. In fact, the binding site of these CAIs is situated in the most variable region of the CA active sites among the 15/16 α-CA isoforms found in vertebrates, humans included [1][2][3][4][5][6][7][8].…”
Section: (Iii) Ca Inhibitors Occluding the Entrance To The Active Sitementioning
confidence: 99%